Alteryx Masterclass - Let's Get Started - We, Dan (Packt Publishing, 2021)
Master the fundamentals of Alteryx for data cleaning and data preparation. About This Video Grasp the fundamentals of Alteryx Clean and prepare data in Alteryx Derive insights from your data In Detail Alteryx is a data preparation and cleaning tool used mainly by data scientists to clean and prepare data. Its effectiveness lies in its user-friendly interface and variety of tools that can be used for data analysis. In this course, you'll learn the fundamentals of Alteryx and work on preparing and deriving insights from your data. You'll begin by getting an introduction to Alteryx and learn how to get your data into Alteryx. You'll learn how Alteryx cleans data in an efficient way, and how to use this to your advantage. You'll use tools such as 'union' and 'replace' to combine and clean your data, 'cross tab' and 'transpose' to pivot your data, and a host of additional useful tools to learn the dynamics of Alteryx. You'll also work on a case study to cement your knowledge of Alteryx. By the end of this course, you'll be a confident data scientist with the knowledge of Alteryx to clean and prepare your data in the best way possible.